Delayed anterior ischemic optic neuropathy after neck dissection - Götte, Karl; Riedel, Frank; Knorz, Michael C.; Hörmann, Karl (Archives of otolaryngology - head & neck surgery, 2000)
There are only 2 published cases of anterior ischemic optic neuropathy (AION) occurring after neck dissection, to our knowledge. We report a case of bilateral AION following neck dissection, discuss the differential diagnoses, and compare the features of this case with those of previously described cases. There were none of the previously described risk factors for the development of AION after head and neck surgery (eg, hypotension, facial edema, or sudden massive hemorrhage) in this case, but there was prolonged diffuse postoperative bleeding. Also, the symptoms did not arise before the fifth postoperative day as they did in the other cases. Prolonged, mild postoperative bleeding is a risk factor for AION. Visual loss during the entire first postoperative week has to be regarded as a complication of surgery, requires the exclusion of several differential diagnoses, and must not be confounded with the patient's confusion or symptoms of withdrawal.Arch Otolaryngol Head Neck Surg 2000;126:220-223-->
Gesehen am 18.05.2022